(Un)doing Diabetes: Representation, Disability, Culture
XIX, 368 p.
Keywords: While the 21st century insulin crisis provokes protest and political dialogue, public conception of diabetes remain firmly unchanged. Popular media representations portray diabetes as a condition couched in lifestyle choices. In the groundbreaking volume (Un)doing Diabetes, authors destabilize depictions so powerful, so subtle, and so unquestioned, that readers may find assertions counterintuitive. (Un)doing Diabetes is the first collection of essays to use disability studies to explore representations of diabetes across a wide range of mediums- from Twitter to TV and film, to theater, fiction, fanfiction, fashion and more. This disability studies approach to diabetes locates individual experiences of diabetes within historical and contemporary social conditions. In undoing diabetes, authors deconstruct assumptions the public commonly holds about diabetes, while writers doing diabetes present counter-narratives community members create to represent themselves. This collection will be of interest to scholars, activists, caregivers, and those living with diabetes.